ChemInform Abstract: P3‐Type Layered Sodium‐Deficient Nickel‐Manganese Oxides: A Flexible Structural Matrix for Reversible Sodium and Lithium Intercalation. Issue 3 (29th December 2015) - Kalapsazova, Maria; Ortiz, Gregorio F.; Tirado, Jose L.; Dolotko, Oleksandr; Zhecheva, Ekaterina; Nihtianova, Diana; Mihaylov, Lyuben; Stoyanova, Radostina
Abstract: P3‐Nax Ni0.5 Mn0.5 O2 (x = 0.50, 0.67) and P2‐Na0.66 Ni0.33 Mn0.66 O2 are prepared by thermal decomposition of freeze‐dried Na, Ni, and Mn acetate precursors in O2 at 400 °C followed by annealing in air (700 °C, 24 h).